PERUBAHAN PENGGUNAAN LAHAN HUTAN SEKITAR SUNGAI KAMPAR, RIAU - Ishak Sumantri; Machfudh Wesman E; Haryono Haryono (Jurnal Penelitian Hasil Hutan, 1987)
This study is to evaluate the trend of forest  land-use change as a result of  the community's   activities in pursuing  its need for settlement  and land cultivation  in forest  land in the vicinity of Kampar  river, Riau. To understand the trend of forest  land utilization change, 4 data resource references including aerial photo 1964, general view of 1974 forest  map,  1982 land use map, and a ground  check in 1984, have been used. During two periods i.e., in the years from 1964 to 1974, and from  1974 to 1984, it is known  that an invation  occured into both limited production  forest and conversion forest  in the Sub Districts of Kampar Kiri and Sengingi. An analysis of data, using "population  pressure"  and  "location-quotient formulation"  technique shows  that population  pressure  and low income  causes invation  into  the forest  areas